Avaliação dos efeitos da reeducação postural global (rpg) em pacientes com espondilite anquilosante - Silva, Eliane Maria da (2010)
The Ankylosing Spondylitis (AS) is a chronic inflammatory disease that primarily affects the axial skeleton, leading to limitation of spine mobility and functional disability. Physical therapy, especially exercise, is an important part in your treatment. The Global Postural Reeducation(GPR),a method that uses stretching based on evaluation of muscular chains, with significant interference in postural changes may be a complementary alternative for the treatment of this disease. The aim was to evaluate the effects of Global Postural Reeducation (GPR) in patients with Ankylosing Spondylitis (AS) and compare GPR with group conventional segmental self-stretching and breathing exercises. This is a controlled interventional study of 38 patients divided into 2 groups: a GPR group (n = 22) and a control group (n = 16). Both groups were treated over four months. With the GPR group patients, positions that stretched the shortened muscle chains were used. With the control group patients, conventional segmental self-stretching and breathing exercises were performed. The variables analyzed were: pain intensity, morning stiffness, spine mobility, chest expansion, functional capacity (Health Assessment Questionnaire - Spondyloarthropathies - HAQ-S), quality of life (Medical Outcome Study Short Form 36 Healthy Survey-SF-36), and disease activity (Bath Ankylosing Spondylitis Disease Activity Index - BASDAI). Statistical analysis was used with a significance level of p < 0.05. There was a statistically significant difference for all the parameters analyzed between pre and post-treatment in both groups. In the inter-group comparison the GPR group showed a statistically significant improvement in morning stiffness (p = 0.01), spine mobility parameters, except finger-floor distance (p = 0.11), in chest expansion (p = 0.02), and in the physical aspect component of the SF-36 (p = 0.00).Finally, we observed that this sample of patients with AS ,treatment with RPG 60 seems to have a better response in some clinical measures, than the conventional self stretching performed in groups. Further studies are needed to further evaluate this therapeutic alternative in the EA